Dampak Perangkat Digital terhadap Kesehatan Fisik, Sosial, dan Mental Siswa: Kasus Siswa Sekolah Menengah di Sri Lankan International School Riyadh (SLISR) - Abeywickrama, Rohan (Linguistika Kultura, 2025)
With the advancement of electronic devices, life has become easier and much quicker. However, overuse of internet-assisted applications and tools as well as online platforms can harm one's physical, mental, and social health by increasing anxiety, depression, and isolation. The current study examines how digital disturbance affects students' mental, social, and physical well-being and informs of how to mitigate those detrimental impacts, thereby enhancing productivity, broadening skills, and improving academic achievements. This qualitative study employed semi-structured interviews to gather information from ten students in grade 11 and 5 parents at the Sri Lankan International School, Riyadh. The findings of the study were analyzed using the Thematic Analysis (TA) framework. The results indicated that the increasing reliance on digital devices has led to a range of negative consequences for students' physical, social, and mental health, which in turn significantly affects their academic performance. These adverse effects are evident in various academic challenges, including reduced academic quality, increased workloads, absenteeism, boredom, poor organization, difficulties in understanding educational tasks, inadequate preparation, and ultimately, low learning achievement. Students' screen time is largely increasing as a result of the pressure on teachers to incorporate technology into the majority of their lessons. The findings point to the need to reduce students’ screen time as well as the harmful effects. This study has raised awareness of the detriments of utilizing digital devices in the classroom and made recommendations on how to integrate them more successfully into the personal and academic lives of students. The study has implications for ESL teachers, syllabus designers, and school management.